Development of a parametric estimating model for technology-driven deployment projects - Watson, Rudy J.; Kwak, Young Hoon (2004 Winter Simulation Conference, 2004)
The purpose of this paper is to define the process used to develop a parametric estimating model and to explain the use of the model as it allows a non subject matter expert to predict the cost of deployment of a technology-driven project with improved accuracy.The overall objective is to define criteria for organizations to use as a rule of thumb estimating model for determining potential resource requirements during the pre-concept and concept phase of a technology-driven project.The use of the model will determine the complexity level of a project and then using a matrix simulating the task complexity knowledge of a deployment subject matter expert, the organization deployment resource required will be estimated based upon responses to certain inquiries. The user of the model will then have the capability to modify the output to derive their specific deployment estimates.